A case on papillary thyroid carcinoma with intraluminal tracheal extension: A Malaysian experience and literature review - Alex Zhi, Jian Ho; Abdul Wahab, Azwan Halim; Rozhan, Atikah (Springer Nature, 2024)
Papillary thyroid carcinoma (PTC) is a common malignancy originating from the thyroid gland. In rare cases, it can invade the trachea, resulting in airway obstruction. Subsequent surgical planning may be complicated as the technique selected depends on a case-by-case basis. Here, we report a case of PTC with tracheal involvement and a literature review on the latest surgical options. A 56-year-old gentleman presented with an anterior neck swelling of 3 x 3 cm for 3 months. Flexible endoscopy showed irregular mass in the subglottic region. Subsequent aspiration for cytology confirmed a diagnosis of PTC. Neck contrast enhanced computed tomography showed an ill-defined lesion in the right thyroid (3.1 x 3.8 x 2.9 cm) with a subtle irregularity of the adjacent tracheal wall suggestive of infiltration. The findings indicated a clinical staging of cT4aN0M0 (Stage III) with Shin’s staging of Stage IV. The patient underwent a total thyroidectomy and a single-stage partial cricoid-tracheal resection with anastomosis. There were no immediate post-operative complications reported. Unfortunately, the patient suffered from pulmonary embolism, which eventually resulted in his demise. A subsequent histopathology report confirmed the diagnosis of PTC. Surgical planning for such cases may be complicated. The risk of recurrent laryngeal nerve injury is increased as the site of resection is close to the nerve. Multiple intraoperative nerve monitoring systems may be required. Meticulous planning of intraoperative airway management is needed as a large intraluminal tumor may interfere with intubation. Generally, extensive tracheal invasion would require radical surgical approaches such as circumferential resection and total laryngectomy. Less extensive cases can be treated with shave excision or window resection. PTC with tracheal invasion is an uncommon condition, and surgical excision is indicated for cases with high Shin’s staging